Requirement for Dot1l in murine postnatal hematopoiesis and leukemogenesis by MLL translocation - Jo, Stephanie Y.; Granowicz, Eric M.; Maillard, Ivan; Thomas, Dafydd; Hess, Jay L. (Blood, 2011)
Disruptor of telomeric silencing 1-like (Dot1l) is a histone 3 lysine 79 methyltransferase. Studies of constitutive Dot1l knockout mice show that Dot1l is essential for embryonic development and prenatal hematopoiesis. DOT1L also interacts with translocation partners of Mixed Lineage Leukemia (MLL) gene, which is commonly translocated in human leukemia. However, the requirement of Dot1l in postnatal hematopoiesis and leukemogenesis of MLL translocation proteins has not been conclusively shown. With a conditional Dot1l knockout mouse model, we examined the consequences of Dot1l loss in postnatal hematopoiesis and MLL translocation leukemia. Deletion of Dot1l led to pancytopenia and failure of hematopoietic homeostasis, and Dot1l-deficient cells minimally reconstituted recipient bone marrow in competitive transplantation experiments. In addition, MLL-AF9 cells required Dot1l for oncogenic transformation, whereas cells with other leukemic oncogenes, such as Hoxa9/Meis1 and E2A-HLF, did not. These findings illustrate a crucial role of Dot1l in normal hematopoiesis and leukemogenesis of specific oncogenes.